(untitled) (Research, Society and Development, 2022)
Vaginismus is a persistent involuntary contraction of the vagina’s musculature that interferes with penetration, preventing sexual intercourse and possibly compromising interpersonal and marital relationships, for which some physiotherapy strategies have been proposed. The causes of this sexual dysfunction can be due to several factors, including, mainly, pain in the first sexual act, traumatic experiences in childhood, sociocultural causes (church and family, taboos and beliefs, sexual inhibition, emotional conflicts, lack of communication between the couple), physical trauma, surgical sequelae and sexual abuse. A bibliographic review was carried out, based on PubMed and SciELO databases, between the years 2000 and 2018. As for the management of the problem, physiotherapy proves to be effective and necessary to address and treat the complaint, as it involves several resources and techniques for understanding and addressing vaginismus, emphasizing the importance of diagnosis and a thorough evaluation. It was concluded that physiotherapy has a significant effect on the quality of life and sexual satisfaction of women with this sexual disorder, especially for those who have suffered trauma from sexual violence.